Study on the effect of ash in coal liquefaction residue on the preparation of high-density carbon materials by induced polycondensation. Issue 1 (31st March 2022) - Luo, Huafeng; Li, Tongda; Wang, Fuquan; Cui, Kai
ABSTRACT: Coal liquefaction residues have been used to prepare microporous and mesoporous carbons. Although these carbon materials have abundant pore sizes, their mechanical strength is poor, but cannot meet the demand for metallurgical coke in the industrial field. Based on the above-mentioned defects of carbon materials, a new method was proposed to prepare high-density carbon materials by in-situ addition of furfural in coal liquefaction residues at 450°C by inducing polycondensation. In order to study the influence of minerals and sulfur content in the coal liquefaction residue on the density of the induced polycondensation carbon material, it is proposed to firstly remove the ash and sulfur content of the coal liquefaction residue by hydrochloric acid and hydrofluoric acid, and then the changes of density and structure of carbon materials prepared by induced polycondensation were studied. The results showed that the treatments of HCl and HF have little effect on the pyrolysis of coal liquefaction residues, but only slightly shift the maximum pyrolysis rate temperature to the high temperature section. The 28.96%, 65.33% of ash and 2.42%, 46.06% of sulfur content in the coal liquefaction residue can be removed by the HCl and HF, respectively, but have little effect on the contained organic matter. The mass of organic components of YH-polymer, YH-HCl-polymer and YH-HF-polymer in N-methylpyrrolidone solvent decreased by 10.3%, 2.0% and 5.0%, respectively, indicating that the deashing treatment of coal liquefaction residues can further improve the polymerization degree of condensation. The removal of minerals can further promote the increase of thermal stability and disorder of the polymer, and the microcrystalline structure of the obtained product after further carbonization is regular and tends to graphitize. The density and sulfur content (0.81%) of the carbon materials produced by HF removing ash in coal liquefaction residue have reached the metallurgical coke standard.